Nonlinear dynamics of marine rotor-bearing system coupled with vibration isolation structure subject to ship rolling motion - Xie, Xuan; Li, Ming; Du, Xiaolei (Applied Mathematical Modelling, 2022)
•We considered the effect of ship rolling motion and nonlinear oil film force.•We considered the rotation of the raft and established a mathematical model.•We studied the nonlinear dynamic behaviors of the rotor and the raft frame. This study focuses on the nonlinear dynamic behavior of a marine rotor-bearing system coupled with vibration isolation structure under ship rolling motion. After considering the effect of the nonlinear oil film force and the ship rolling motion, a mathematical model is established based on Lagrange's equation. By employing a numerical method, the dynamic steady-state response of the system is analyzed, such as the orbits of the rotor and its Poincaré maps, spectrum waterfall diagram, and the displacements and frequency spectrum diagram of the raft frame. We also studied the effects of the rotor speed, the amplitude and frequency of ship rolling on the marine rotor-bearing system coupled with isolation structure under ship rolling motion. The results indicates that response of the rotor shows obvious nonlinear dynamic behaviors such as amplitude jumping, bifurcation and chaos due to the influence of the nonlinear oil film force and the ship rolling motion. As the rotor speed increases, the motion of the rotor experiences the process of quasi-periodic and chaos vibration. Both the amplitude and frequency of ship rolling have effects on the amplitude of the rotor and the raft frame. Moreover, the rotation angle of the raft frame is greatly influenced by the amplitude and frequency of ship rolling, and it is necessary to control the vibration attitude of the raft frame.